Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fneur.2022.834240
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Dysphagia and Pneumonia in Acute Stroke Patients: A Systematic Review and Meta-Analysis

Abstract: BackgroundDysphagia is a common complication after stroke and is associated with the development of pneumonia. This study aimed to summarize the relationship between dysphagia and pneumonia in post-stroke patients.Materials and MethodsArticles published up to November 2021 were searched in the PubMed, Embase, Cochrane library, and Scopus databases. Studies that investigated the development of pneumonia in acute stroke patients with and without dysphagia were included. The methodological quality of individual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Swallowing dysfunction can propitiate the introduction of oral content including food or fluids such as saliva in the respiratory tract, potentially leading to aspiration pneumonia 12,13 . The correlation between dysphagia and aspiration pneumonia has previously been proven in longitudinal studies 14 and a recent systematic review found dysphagia to be a risk factor for pneumonia in patients attended for stroke 15 . The higher risk of aspiration pneumonia in patients with dysphagia is also associated with increased hospital stay and mortality risk 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swallowing dysfunction can propitiate the introduction of oral content including food or fluids such as saliva in the respiratory tract, potentially leading to aspiration pneumonia 12,13 . The correlation between dysphagia and aspiration pneumonia has previously been proven in longitudinal studies 14 and a recent systematic review found dysphagia to be a risk factor for pneumonia in patients attended for stroke 15 . The higher risk of aspiration pneumonia in patients with dysphagia is also associated with increased hospital stay and mortality risk 5 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 The correlation between dysphagia and aspiration pneumonia has previously been proven in longitudinal studies 14 and a recent systematic review found dysphagia to be a risk factor for pneumonia in patients attended for stroke. 15 The higher risk of aspiration pneumonia in patients with dysphagia is also associated with increased hospital stay and mortality risk. 5 In the context of the quality and patient safety improvement initiatives in our tertiary hospital in Barcelona, concerns about the incidence of aspiration pneumonia among in-patients triggered the will to quantify the prevalence of dysphagia and its correlation with pneumonia.…”
mentioning
confidence: 99%
“…The stage of dysphagia may be related to stroke and tracheostomy. Chang et al reported that in patients with acute cerebral infarction, dysphagia usually occurs in the oral and pharyngeal stages [ 38 ]. Betts et al reported that the tube cuff could obstruct the pharyngeal pathway directly [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cluster : Clinically relevant studies of post-stroke pneumonia Clinical symptoms of dysphagia could contribute to the development of post-stroke pneumonia (57). Data show that up to 50% of patients with post-stroke presented clinically with dysphagia, and nearly half of them were at risk of aspiration (58).…”
Section: Research Hotpots Of Global Publicationsmentioning
confidence: 99%